The Impact of Financial Technology on Improving The Performance of The Banking Sector: an Applied Study In Iraq for The Period (2010-2022) - Ridha, Iman (Journal of Economics, Assets, and Evaluation, 2025)
This research aims to determine the impact of financial technology (financial technology, specifically point-of-sale (POS) devices, e-wallets, and the number of ATMs) on improving the performance of the banking sector (return on assets, return on equity, capital adequacy, management efficiency, liquidity ratio, and security ratio) through an applied study in Iraqi banks during the period (2010-2022). A standard model was used to measure the impact of financial technology on the banking sector's performance and its various indicators. To achieve this objective, a standard analysis method was used to illustrate the impact of financial technology on the performance of the Iraqi banking sector, using Eviews 10 software and Amos Graphics software for graphing. The study's findings concluded that financial technology has contributed to improving the productivity of banking operations through the integration of technology and computing techniques, particularly in developed countries.